5-HT1F Receptor Agonist Ameliorates Mechanical Allodynia in Neuropathic Pain via Induction of Mitochondrial Biogenesis and Suppression of Neuroinflammation - Zhang, Long-Qing; Zhou, Ya-Qun; Li, Jia-Yan; Sun, Jia; Zhang, Shuang; Wu, Jia-Yi; Gao, Shao-Jie; Tian, Xue-Bi; Mei, Wei (Frontiers in Pharmacology, 2022)
Neuropathic pain is a devastating disease affecting millions of people worldwide. Serotonin (5-hydroxytryptamine, 5-HT) has long been involved in pain modulation. Several lines of evidence indicate that 5-HT1F receptor agonists are potent inducers of mitochondrial biogenesis. In this study, we tested the hypothesis that 5-HT1F receptor agonist ameliorates mechanical allodynia in neuropathic pain via induction of mitochondrial biogenesis and suppression of neuroinflammation. Here, male Sprague-Dawley rats were used to establish neuropathic pain via spared nerve injury (SNI). Paw withdrawal threshold was used to evaluate mechanical allodynia. Real time polymerase chain reaction was used to examine the mitochondrial DNA (mtDNA) copy number. Western blot and immunofluorescence were used to examine the expression of target proteins. Our results showed that mitochondrial biogenesis was impaired in the spinal cord of SNI rats. Moreover, activation of PGC-1α, the master regulator of mitochondrial biogenesis, attenuated established mechanical allodynia in neuropathic pain rats. Besides, neuronal 5-HT1F receptor was significantly downregulated in the spinal cord of neuropathic pain rats. Furthermore, selective 5-HT1F receptor agonist Lasmiditan attenuated established mechanical allodynia in neuropathic pain rats. Finally, Lasmiditan treatment restored mitochondrial biogenesis and suppressed neuroinflammation in the spinal cord of SNI rats. These results provide the first evidence that Lasmiditan ameliorates mechanical allodynia in neuropathic pain via induction of mitochondrial biogenesis and suppression of neuroinflammation in the spinal cord. Mitochondrial biogenesis inducers may become encouraging therapeutic option for the management of neuropathic pain.